2003
DOI: 10.1046/j.1365-2265.2003.01917.x
|View full text |Cite
|
Sign up to set email alerts
|

The androgen receptor gene CAG polymorphism is associated with the severity of coronary artery disease in men

Abstract: The shorter CAG repeat of the AR gene is associated with more severe CAD, which suggests a role for the sensitivity to androgens in the increased frequency of CAD in males. In addition, a protective role of endogenous oestrogen, which is higher in the longAR subgroup, can contribute to the observed difference.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
77
3
3

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(92 citation statements)
references
References 57 publications
9
77
3
3
Order By: Relevance
“…Our results contrast with a recent study that found a weak association between short AR alleles with fewer CAG repeats and coronary artery stenosis but not with carotid intima thickness (20 ). That study, however, enrolled only a limited number of patients and controls (134 in total).…”
Section: Discussioncontrasting
confidence: 55%
“…Our results contrast with a recent study that found a weak association between short AR alleles with fewer CAG repeats and coronary artery stenosis but not with carotid intima thickness (20 ). That study, however, enrolled only a limited number of patients and controls (134 in total).…”
Section: Discussioncontrasting
confidence: 55%
“…However, these women belonged to a highly selected group with possibly multiple predisposing factors and the observed effect was independent of other factors. Thus, although these results cannot be extrapolated to the general population, they show that within this group of women the genotype of sex hormone receptor may be of importance for the severity of CAD as it has been previously shown for men (19,25,57), obviously reflecting the long-term effects of sensitivity to hormonal action.…”
Section: Discussionmentioning
confidence: 75%
“…7 In 1 casecontrol study, men in the lowest CAG repeat quartile were more likely to have significant coronary heart disease than those in the highest quartile. 3 In contrast, no association between the number of CAG repeats and MI was observed in another case-control study in men, although those with fewer CAG repeats did have lower HDL levels. 8 Limitations of the present study include generalizability and potential biases.…”
Section: Rexrode Et Al Androgen Receptor Variation and Risk Of MI Andmentioning
confidence: 78%
“…Results were similar for cutpoints of Ն22 or Ն23 repeats. 3,6 In conditional logistic regression there was no significant association between repeat length and any of the end points, nor was any association observed when CAG repeat was modeled as a log-transformed continuous term. …”
mentioning
confidence: 99%